Incomplete resection rate of cold snare polypectomy: a prospective single-arm observational study - Matsuura, Noriko; Takeuchi, Yoji; Yamashina, Takeshi; Ito, Takashi; Aoi, Kenji; Nagai, Kengo; Kanesaka, Takashi; Matsui, Fumi; Fujii, Mototsugu; Akasaka, Tomofumi; Hanaoka, Noboru; Higashino, Koji; Tomita, Yasuhiko; Ito, Yuri; Ishihara, Ryu; Iishi, Hiroyasu; Uedo, Noriya (Endoscopy, 2017)
Background and study aims Cold snare polypectomy (CSP) is considered to be safe for the removal of subcentimeter colorectal polyps. This study aimed to determine the rate of incomplete CSP resection for subcentimeter neoplastic polyps at our center.Patients and methods Patients with small or diminutive adenomas (diameter 1 – 9 mm) were recruited to undergo CSP until no polyp was visible. After CSP, a 1 – 3 mm margin around the resection site was removed using endoscopic mucosal resection. The polyps and resection site marginal specimens were microscopically evaluated. Incomplete resection was defined as the presence of neoplastic tissue in the marginal specimen. We also calculated the frequency at which the polyp lateral margins could be assessed for completeness of resection. Results A total of 307 subcentimeter neoplastic polyps were removed from 120 patients. The incomplete resection rate was 3.9 % (95 % confidence interval [CI] 1.7 % – 6.1 %); incomplete resection was not associated with polyp size, location, morphology, or operator experience. The polyp lateral margins could not be assessed adequately for 206 polyps (67.1 %). Interobserver agreement between incomplete resection and lateral polyp margins that were inadequate for assessment was poor (κ = 0.029, 95 %CI 0 – 0.04). Female sex was an independent risk factor for incomplete resection (odds ratio 4.41, 95 %CI 1.26 – 15.48; P  = 0.02).Conclusions At our center, CSP resection was associated with a moderate rate of incomplete resection, which was not associated with polyp characteristics. However, adequate evaluation of resection may not be routinely possible using the lateral margin from subcentimeter polyps that were removed using CSP.Trial registered at University Hospital Medical Information Network (UMIN 000010879).